The library in the twenty-first century - Brophy, Peter, 1950- (London : Facet, 2007)
Social, cultural and technological developments are revolutionizing library services. The way ahead for the profession is now generally seen as a practical blend of traditional and electronic materials with integrated support services which fit seamlessly into users' normal ways of working. This is leading to a fundamental rethinking of the role of the library in society. Drawing on the author's recent research, this timely second edition of The Library in the Twenty-first Century offers a clear new model of how traditional and electronic sources can co-exist in the library of the future, building on the previous work by focusing on the library as a vehicle for encouraging creativity as well as a provider of information resources. It is now commonplace that libraries have a major role to play as expert intermediaries, helping users to gain access to the tools needed for effective acquisition and use of information, within the broader context of the networked information world. But it is beginning to be recognized that they still have a profounder role within their communities, and this book emphasizes that beyond the intermediary role is the vital requirement to promote understanding and engagement. -- Back cover.
Part I. What is a library? 1. Libraries in the modern world --- 2. What is a library? The view from the sectors --- 3. What is a library? Cross-sectoral models --- 4. What is a library? The profession's view ---5. What is a library? Digital libraries --- 6. What is a good library? ---- Part II. Future libraries. 7. Linking users to resources --- 8. Beyond the intermediary --- 9. The library user --- 10. The information universe --- 11. Envoi.
Previous edition: 2001.
Includes bibliographical references (pages 213-232) and index.
Self-Renewing
NLJCols20082021
Keywords: Amerika Haus Berlin -- Video Lending Library; Library science -- Philosophy; Information resources management; Information resources; Libraries; Libraries -- organization & administration; Library Services; Information Science; Library Science [MESH]; Library Science; Biblioth eques; Biblioth economie; Biblioth eque electronique; Futur; Information resources; Information resources management; Library science -- Philosophy; Zukunft; Bibliothek -- Benutzung